Metáforas e sua representatividade na gestão acadêmica - Vignati, Monia Lavra (2019)
Social organizations are essentially symbol-oriented, from which organizational agents are constantly thinking, reflecting and acting, based on images, discourses, decisions and actions. Among the different types of symbols present in the literature is th